PEMETAAN CITRA 3D UNTUK PERENCANAAN KOTA BERBASIS FOTOGRAMETRI MENGGUNAKAN KAMERA DAN RASPBERRY PI - Setyawan Ajie Sukarno; Aris Budiyarto; Muhammad Fadrial (P3M Politeknik Negeri Indramayu, 2024)
Indonesia is currently undergoing digital development efforts, one of which is smart city. Spatial planning requires accurate data so that the results match the factual conditions. So, to get a map of a city, geospatial data is needed which is obtained by mapping. Currently, the mapping carried out is still predominantly using conventional methods. The maps processed by conventional mapping are very limited and cannot be processed further. In this research, digital mapping was carried out using aerial technology. Digital mapping is carried out using the aerial photography method which is carried out by utilizing a UAV (Unmanned Aerial Vehicle). The aerial photography/photogrammetry method with a camera can provide information related to the location and shape of objects in very high resolution. The results of the capture method are used to form a 3D map. the results in testing the height of the photo taking have an altitude RMSE value of 2.321 MDPL and 2.295 MDPL. The tests carried out have met the requirements for LOD level 1, which has an RMSE value below 5 meters. In testing light conditions of 60 LUX and 600 LUX, then with different resolution levels for 3D map results. It can be concluded that with good lighting test conditions and high photo resolution, the lowest 3D map accuracy value is 14.3% and the highest is 100%.